Electronic and paper based data collection methods in library and information science research: A comparative analyses. Issue 9 (12th October 2015) - Tella, Adeyinka
Abstract : Purpose: – This study aims to examine a comparative analysis of electronic- and paper-based data collection methods. Design/methodology/approach: – Survey research approach was adopted to conduct the study. A total of 500 library and information science (LIS) researcher/information professionals selected randomly from seven states in Nigeria represent the sample for the study. A self-designed questionnaire was used to gather data from the respondents. Six objectives were developed to guide the study. Findings: – The findings reveal that there is preference for paper-based than the electronic-based data collection methods, and similarly, respondents indicated they cannot use any other data collection methods other than paper-based. Electronic data collection method is beneficial in terms of gathering a representative sample within a short period compared to the paper-based method. The researcher has control over access to the survey in the paper-based method compared to the electronic method, and there is opportunity to monitor the progress of the research and clarify ambiguity by the researcher. The electronic method is limited in terms of collecting data from only the respondents who are computer-literate with good Web skills, while the paper-based method is limited by higher attrition rate, money and time consumption. Research limitations/implications: – The study did not consider the time needed to gather data with each method or the amount of time needed for data entry, cleaning and coding. It is possible that a time-motion study would reveal clear superiority of either one method or the other. The total sample of participants in the study is also limited, considering the total number of LIS researcher/information professionals in Nigeria. Practical implications: – The study has underlined the value of electronic/Web-based collection as a cost- and time-saving instrument in modern LIS research. Regardless of method and trial, electronic data collection could fulfill in all examined parameters, its promises, realizing cost savings of up to a 50 per cent in comparison with the paper-based data collection method. Originality/value: – The paper is solely the idea of the author.